Altered thrombin generation with prothrombin complex concentrate is not detected by viscoelastic testing: an in vitro study - Hofmann, Nikolaus; Schöchl, Herbert; Zipperle, Johannes; Gratz, Johannes; Schmitt, Felix; Oberladstätter, Daniel (British journal of anaesthesia, 2025)
Background - Bleeding guidelines currently recommend use of viscoelastic testing (VET) to direct haemostatic resuscitation in severe haemorrhage. However, VET-derived parameters of clot initiation, such as clotting time (CT) and activated clotting time (ACT), might not adequately reflect a clinically relevant interaction of procoagulant and anticoagulant activity, as revealed by thrombin generation assays. The aim of this study was to evaluate the ability of CT and ACT to indicate thrombin generation activity. - Methods - Citrated whole blood obtained from 13 healthy volunteers underwent a 50% crystalloid dilution (DL-50%), followed by spiking with four-factor prothrombin complex concentrate (DL-50% + 4F-PCC). Changes in thrombin generation activity were compared with the VET parameters CT and ACT derived from four commercially available viscoelastic devices (ROTEM® Delta, ClotPro®, TEG®6s, and Quantra®) and standard coagulation tests. - Results - Dilution of whole blood resulted in a marked increase in velocity index, peak height, and endogenous thrombin potential (all P<0.01), with a further substantial increase after spiking with 4F-PCC (all P<0.001). In contrast, CT and ACT were significantly prolonged in response to DL-50% on all devices (all P<0.05). Subsequent spiking of diluted blood with 4F-PCC had no impact on CT and ACT derived from VET analysers, but it restored standard coagulation tests without reaching baseline values (all P<0.01). - Conclusions - Upregulated thrombin generation parameters after PCC spiking were not displayed by CT, ACT, or standard tests. Our results do not support treatment algorithms using prolonged CT or ACT as a trigger for administration of PCC to augment thrombin generation.
Online verfügbar: 04. Januar 2025, Artikelversion: 20. April 2025
Gesehen am 21.10.2025